INTERNAL AUDIT AN FIRST AID SOLUTION WHO CAN LEAD TO EFFICIENT USE OF EU FUNDS FOR RURAL ECONOMIC DEVELOPMENT IN ROMANIA - Ispas, Simona; Dutescu, Adriana; Stanila, Oana (Economics of Agriculture, 2012)
In 2007, the real stake for Romania in the relationship with the European Union was not the effective adhesion, which was a certain fact but only a matter of time. The real stake was Romanias capacity in absorbing the substantial funds that the union would provide access to. In other words the real stake at that moment was the adequate capacity of community funds absorption. According to the analyse of the Authority for Coordination of Structural Instruments, between 2007-2013, Romania had and still has at its disposal, funds in total amount of 19,2 mld EURO or 81 mld RON that should be absorbed by the end of 2015 (this amount does not include the agricultural funds). Taking into account that at the moment our country absorbed almost 9 mld RON, which means 11,06% from the total amount, in order to attract the entire sum it would be necessary that by the end of 2015, payments of approx. 14 mld should be performed yearly, amount 7 times higher than in 2010. In conformity with the report prepared by the Council Tax and recently published, at the end of 2010, Romania was the last country, out of 6 analised, regarding the absorption rate between 2007-2013 of 8,6%, behind Bulgaria (10,2%), Czech Republic (12,4%), Poland (20,4%),Estonia (26%) and Latvia Republic (29%). Regarding the European fund dedicated to the rural development, Payments Agency for Rural Development and Fisheries approved 30.500 projects through the National Project of Rural Development 2007-2013, from the official starting date – 3 rd of March 2008, until the15 th of July 2011, in amount of approx of 4 mio EURO. This amount represents approx. 40% from the total sum dedicated to the Romanian agriculture, rate that was achieved in 4 and a half years. In order to spent the rest of 60%, Romania has at its disposal 2 and a half years. As a first measure in this situation, I consider that the development of rural segment can be influenced by the internal audit department, which can insure and advise through its actions a better fund administration and a substantial improvement of the public activities. This department can also help the Agency to fulfil its targets through a methodical and systematic approach, action which would also improve the efficiency and efficacy of the system, of the administration processes and controlling process.